The Awakening of Islamic Pop Music - Otterbeck, Jonas (Edinburgh University Press, 2021)
Awakening - an Islamic media company formed in London - has created the soundtrack to many Muslim lives during the last two decades. It has produced three superstars (Sami Yusuf, Maher Zain and Harris J.) among a host of other artists. As the company celebrates their first 20 years in the industry, Jonas Otterbeck examines their remarkable rise to success and their established reputation as one of the most important global enterprises producing pop music inspired by Islam.Otterbeck thoroughly describes the history and development of new Islamic popular music genres, in particular pop-nashid and Islamic pop, for the first time. He argues that Awakening - a company with the ambition to portray itself as Islamic - is best understood in relation to the ethical turn in Islamic thinking. In analysing the turn to ethics, he explores how the Islamic pop industry is, in effect, altering the very formulations of Islamic thought. Closely examining the ethical masculinity of the Awakening artists, alongside their personas in songs, on stage and on social media, the book analyses how popular culture and the creative arts challenge Islamic (re)thinking.